UNLEASHING HIDDEN POTENTIALS: THE EFFECT OF SELF-RECORDING IN LANGUAGE ASSESSMENT - Darong, Hieronimus Canggung (Premise: Journal of English Education and Applied Linguistics, 2024)
The purpose of this study was to know the effects of using self-recording in peer and self-assessment in language learning. This mixed-method research design with post-test control groups utilized speaking tests, rubrics, self-assessment checklists, interview guides, and teaching scenarios to collect data. Instrument preparation, validation, and reliability tests were all part of rigorous data-gathering procedures. Using stratified random sampling, participants were divided into control and experimental groups. Each group received different treatment, using self-recording for peer and self-assessment in the experimental group and traditional oral presentations in the control group. Speaking performances by students were recorded for self-and peer assessment, whereas the control group was assessed using a teacher's criteria. The results of the posttest showed that the experimental group fared much better than the control group, demonstrating the superior effectiveness of self-recording in enhancing speaking skill. In addition, the results of the interview confirmed that self-recording is meaningful for self-control, feedback, time-shifted assessment, equity, and fairness. More importantly, the transformative power of self-recording in assessments highlights the critical function of self-recording in strengthening self-regulation abilities. Thus, in educational and assessment contexts, this technique has the potential to unleash hidden self-regulation capacities, resulting in deep personal development and positive transformations.